Economics of Mustard Seed Production - An Analytical Study from Terai Zone of West Bengal - Layek, Nityananda; Mula, Gobinda; Sarkar, Ashutosh; Roy, Bidhan (Indian Journal of Extension Education, 2021)
The study analysed the economics of mustard seed production to determine the cost of cultivation, technicalÂ efficiency, allocative efficiency, marketing and constraints in Terai zone of North Bengal during 2018-19. The multistage sampling technique was used to select 60 mustard seed growers. On an average 40.50 per cent of net cropped area was devoted for seed production programme. At 2018-19 prices, the Total Variable Cost of cultivation (R/acre) was observed R 20135.70 and R 18923.54 respectively for seed and non seed conventionalÂ production. The net return (GI-Cost C3) in seed production (R 9138.67/acre) revealed 128.56 per cent higher than conventional production practice. Based on Cost C3, the evaluated input-output ratio for seed productionÂ examined as 1:1.32. The overall contribution of different resources in variation of income found 76.72 per cent (R2 = 0.7672). The factors viz. seed, inorganic fertilizers and agrochemical revealed significant impact on money return (at 5% level each). The MVP and RUE were worked out and found positive for the resources viz. human labour, inorganic fertilizers and irrigation. In respect of marketing, although marketing efficiency was observed to be ranging from 120 to 175 per cent but producers' share in consumer rupee revealed below 65 per cent only for value addition in successive stage. Diseases and pest attack, low price of output, weed infestation, non-availability of credit and high price of inputs were the major impediments of mustard seedÂ production.